2019
DOI: 10.4274/jcrpe.galenos.2019.2019.0088
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Optimal Short- and Long-term Responses to Paediatric Growth Hormone Therapy

Abstract: It is over sixty years since the first administration of human growth hormone (GH) to children with GH deficiency, and over thirty years since recombinant human GH has been available for treatment of GH deficiency and a wider range of non-GH deficiency disorders. From a diagnostic perspective, genetic analysis, using single gene or Sanger sequencing and more recently next generation or whole exome sequencing, has brought advances in the diagnosis of specific causes of short stature, which has enabled therapy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 103 publications
0
19
0
Order By: Relevance
“…Our results are reassuring in relation to current clinical practice, in which AGHD is usually the last deficiency to be substituted in hypopituitarism. However, they are in contrast to the effects of paediatric growth hormone therapy, in which age of treatment onset is predictive of both growth acceleration during the first year and final height outcome (9). However, growth velocity in children is dependent on more hormonal and anabolic influences than GH per se, such as tempo of puberty and nutritional status.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our results are reassuring in relation to current clinical practice, in which AGHD is usually the last deficiency to be substituted in hypopituitarism. However, they are in contrast to the effects of paediatric growth hormone therapy, in which age of treatment onset is predictive of both growth acceleration during the first year and final height outcome (9). However, growth velocity in children is dependent on more hormonal and anabolic influences than GH per se, such as tempo of puberty and nutritional status.…”
Section: Discussionmentioning
confidence: 98%
“…It is not known whether these changes in SD scores and the likely association of delayed initiation of GHRT result in poorer outcomes. In paediatric growth hormone therapy, it is well known that age of treatment onset is predictive of final height outcome (9). In addition, it has been shown that growth acceleration during the first year is more marked in younger children (10,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adult height data submitted to the EMA for registration of rhGH therapy indicated that both doses had similar effects on adult height; however, the higher dose tended to induce supraphysiological levels of serum IGF-1 during therapy. Hence, the lower dose of 33 μg/kg/day is now recommended by the EMA [26,27].…”
Section: Treatment Of Non-gh Deficiency Disordersmentioning
confidence: 99%
“…Development of the skeletal system that supports body structures and maintenance of its homeostatic state are highly complex processes orchestrated by an elaborate array of gene activities. A frequently occurring developmental skeletal abnormally is short stature, which can arise as part of systemic diseases [1][2][3]. Height gain as the result of bone elongation is driven by chondrogenesis occurring at the growth plate, which is a cartilaginous structure located near the ends of weight-bearing bones in children [4].…”
Section: Introductionmentioning
confidence: 99%